2023
DOI: 10.3390/jpm13030419
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex-Related Effects on Single-Subject Gray Matter Networks in Healthy Participants

Abstract: Recent developments in image analysis have enabled an individual’s brain network to be evaluated and brain age to be predicted from gray matter images. Our study aimed to investigate the effects of age and sex on single-subject gray matter networks using a large sample of healthy participants. We recruited 812 healthy individuals (59.3 ± 14.0 years, 407 females, and 405 males) who underwent three-dimensional T1-weighted magnetic resonance imaging. Similarity-based gray matter networks were constructed, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Thus, our findings indicate continually decreased functional segregation of the CT networks during the age‐related process. This is consistent with previous studies of single‐subject morphological brain networks based on gray matter volume, which found a negative correlation for clustering coefficient and local efficiency with age (Kong et al, 2015 ; Shigemoto et al, 2023 ). However, using the same method as this work, a recent study found that clustering coefficient of CT networks showed an inverted U‐shaped age‐related trajectory (Wang et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, our findings indicate continually decreased functional segregation of the CT networks during the age‐related process. This is consistent with previous studies of single‐subject morphological brain networks based on gray matter volume, which found a negative correlation for clustering coefficient and local efficiency with age (Kong et al, 2015 ; Shigemoto et al, 2023 ). However, using the same method as this work, a recent study found that clustering coefficient of CT networks showed an inverted U‐shaped age‐related trajectory (Wang et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, our results suggest a fluctuant change in functional integration of the CT networks across the adult lifespan: decreasing between ages 18 and 41, then increasing between ages 41 and 57, and finally decreasing until age 88. Notably, the cubic age‐related changes are first reported since none of previous studies utilized the cubic model to examine the age‐related changes in single‐subject morphological brain networks (Kong et al, 2015 ; Shigemoto et al, 2023 ; Wang et al, 2022 ). Moreover, findings from the previous studies were different or even opposite possibly due to different statistical models and network construction methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To predict the patient’s brain age, the support regression model implemented in the LIBSVM ( http://www.csite.ntu.edu.tw/~cjlin/libsvm/ ) toolbox with a linear kernel and default set of parameters was used (i.e., in the LIBSVM: C = 1, v = 0.5). The details of the analytical method were described in a previous study [ 13 ]. For the regression model, the chronological age was considered the dependent variable, whereas the principal components derived from the gray matter voxel intensities were considered independent variables.…”
Section: Case Presentationmentioning
confidence: 99%
“…To predict the patient's brain age, the support regression model implemented in the LIBSVM (http://www.csite.ntu.edu.tw/~cjlin/libsvm/) toolbox with a linear kernel and default set of parameters was used (i.e., in the LIBSVM: C = 1, v = 0.5). The details of the analytical method were described in a previous study 12 . For the regression model, the chronological age was considered the dependent variable, whereas the principal components derived from the gray matter voxel intensities were considered independent variables.…”
Section: Brain Mri Analysismentioning
confidence: 99%